The complete photo guide to outdoor building : from arbors to walkways: 150 DIY projects - Creative Publishing International; Black & Decker Corporation (Towson, Md.) (Minneapolis, Minn. : Creative Publishing International, an imprint of Quarto Publishing Group USA Inc., 2012)
"With the clear step-by-step photos and vivid instructions in this book, you'll have all the information you need to get building"--Cover.
Planning -- Walkways, patios & steps -- Fences & walls -- Decks -- Porches -- Sheds & outbuildings -- Accessories & recreation structures.
Includes bibliographic references.
Includes conversion charts.
Includes index.
Keywords: Outbuildings -- Design and construction -- Amateurs' manuals; Woodwork -- Amateurs' manuals; Decks (Architecture, Domestic) -- Design and construction; Outdoor living spaces -- Design and construction; Do-it-yourself work -- Amateurs' manuals; Building, Wooden -- Amateurs' manuals; Garden structures -- Design and construction; Landscape construction